Health Literacy and the Use of Antenatal Care Services Among Pregnant Women in Coastal Communities: A Systematic Review - La Ode Ali Imran Ahmad; Amran Razak; Muhammad Alwy Arifin (Public Health of Indonesia, 2026)
Background: Maternal mortality remains a major public health problem, and low health literacy among pregnant women is one of its contributing factors, particularly where women struggle to obtain, understand, and use health information during pregnancy. Most evidence on health literacy and antenatal care comes from urban and rural settings, while coastal and island communities which have distinct characteristics and health problems remain understudied. Objective: To synthesise existing evidence on health literacy among pregnant women and its relationship with the use of antenatal care services, with particular attention to coastal community contexts. Methods: This systematic review employed a thematic synthesis approach. Relevant studies were identified through comprehensive searches of electronic databases, including Medline, Embase, PubMed, Google Scholar, and CINAHL, supplemented by website searches and citation tracking. The literature search was conducted between July 2025 and January 2026. Studies were considered eligible if they investigated health literacy and/or the utilization of antenatal or maternal health-care services among pregnant women or related populations and were published in English. Results: Of 2.697 records identified through databases and registers and 11 through other methods, 32 studies were included in the review. The studies were conducted across diverse settings, most commonly in Ethiopia and Germany, with others across Asia, Europe, and Africa. A range of health literacy measurement tools was identified. Conclusion: Health literacy is closely linked to the use of antenatal care services and supports informed decision-making in maternal care. Strengthening health literacy especially in underserved coastal communities  may improve antenatal care utilisation as well as maternal and infant health outcomes. Keywords: health literacy; antenatal care; pregnant women; coastal communities; systematic review